2011
DOI: 10.1074/jbc.m110.169771
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded Protein Response Is Required in nu/nu Mice Microvasculature for Treating Breast Tumor with Tunicamycin

Abstract: Up-regulation of the dolichol pathway, a "hallmark" of asparagine-linked protein glycosylation, enhances angiogenesis in vitro. The dynamic relationship between these two processes is now evaluated with tunicamycin. Capillary endothelial cells treated with tunicamycin were growth inhibited and could not be reversed with exogenous VEGF(165). Inhibition of angiogenesis is supported by down-regulation of (i) phosphorylated VEGFR1 and VEGFR2 receptors; (ii) VEGF(165)-specific phosphotyrosine kinase activity; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 41 publications
5
92
0
Order By: Relevance
“…Multiple evidences from our study link VEGFR2 with blebbishield biology such as, tunicamycin inhibit sphere formation (Figure 5d) and also reported to downregulate VEGFR2. 37 Heparin binds VEGFR2 at the same motif where VEGF-A binds, 38 hence heparin might block sphere formation by interfering VEGF-A engagement with VEGFR2. Furthermore, acidic pH is known to influence VEGF production and bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple evidences from our study link VEGFR2 with blebbishield biology such as, tunicamycin inhibit sphere formation (Figure 5d) and also reported to downregulate VEGFR2. 37 Heparin binds VEGFR2 at the same motif where VEGF-A binds, 38 hence heparin might block sphere formation by interfering VEGF-A engagement with VEGFR2. Furthermore, acidic pH is known to influence VEGF production and bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…Sustained activation of XBP1 results in apoptosis of endothelial cells by activation of a caspase-dependent pathway, inhibition VE-cadherin transcription (Zeng, Zampetaki et al 2009), and increasing Beclin-1-mediated autophagy (Margariti, Li et al 2013). Banerjee and coworkers demonstrated that induction of the UPR by tunicamycin inhibits angiogenesis both in vitro and in vivo via up-regulating thrombospondin-1 (TSP-1, an endogenous angiogenic inhibitor) and by suppressing VEGF-induced activation of VEGF receptor 1 (VEGFR1) and VEGF receptor 2 (VEGFR2) (Banerjee, Lang et al 2011). These results are consistent with our finding (S.X.…”
Section: Upr Signaling In Regulation Of Angiogenic Processmentioning
confidence: 99%
“…The MVC were analyzed as previously described [22]. Five hot spots from each group were evaluated under 200X magnification and microscopic images from each area were collected (ASI C-203) using an Olympus BX53 with the use of bioquant lifescience 2017 program and recorded as MVC.…”
Section: Histological Staining and Microvessel Counts (Mvc)mentioning
confidence: 99%